Automatyczna dekompozycja specyfikacji behawioralnej sprzętowo-programowego mikrosystemu cyfrowego - Stasiak, Andrzej
The wide applied (classic) design process of the hardware-software digital microsystems is preceded with decomposition of the system specification to set of hardware and software components. The assignment of elaborated system components to hardware or software is performed usual manually by designer during the developing process. About 71% projects do not meet implementation constraints (performance, power consumption, time-to-market) or they are just canceled before project ends. In addition, a microprocessor is the main control and processing unit in modern SOPC (System On a Programmable Chip) architectures. This unit executes program instructions in sequence. Performance (number of executed instructions by time) of the microprocessor that is embedded in SOPC is limited by the technical properties of FPGA devices. When the embedded SOPC system is overloaded then summary performance of the system may decrease below expectations because of the main CPU properties.
Keywords: sieci Petriego; model formalny; PLD; HDL